PENGEMBANGAN SISTEM EVALUASI KINERJA GURU BERDASARKAN KOMPETENSI (Kasus di SMK 45 Kota Bima) - , Johan Kurniawan, Dr. Ir. Lukito Edi Nugroho, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The teachersâ low competence has become one problem in improving the quality of education outside Java. This may be caused by their lack of motivation to develop themselves and improve their knowledge. One solution to resolve this problem is creating a supervision system using certain criteria. To do so, a research on an evaluation system for supervising teachersâ work performance was conducted in SMK 45 Kota Bima. This system is developed by exercising a webbased application in which teachersâ work performance is used as a dependent variable, while teachersâ competence and the number of students who pass the examination as the independent variables. The mentioned citeria are then analyzed using statistical computation and the results are used to calculate the amount of incentive paid to the teachers. The value percentage of each criterion is determined by the results of the questionnaires distributed to the decision makersâschool principals and school supervisors. On the other hand, fellow teachers, principal, and students assess the teacherâs work perfomance. The result of the research is a system which can help the decision makers evaluate the teachersâ work performance and later calculate the incentive.